Percolative ability of fungicides and their evaluation against Fusarium root rot of Acacia (Acacia catechu) - Tomar, Manica; Sharma, R C; Chandel, Sunita (The Indian Journal of Agricultural Sciences, 2008)
An experiment was conducted during 2003-04 to study the root rot of Acacia catechu Willd, caused by Fusarium solani (Mart.) Sacc. Out of benomyl, carbendazim, bitertanol, mancozeb, captaf, penconazole, difenoconazole, hexaconazole, propineb, iprodione + carbendazim, metalaxyl + mancozeb, carbendazim + mancozeb, and carbendazim + mancozeb tested in vitro at 100, 250 and 500 ppm concentrations for systemic fungicides and non-systemic at 250, 500 and 1 000 ppm, while EBI fungicides at 50, 100 and 250 ppm concentrations, carbendazim, followed by benomyl and iprodione + carbendazim were found effective in suppressing the mycelial growth of the fungus. The fungicides performed best in vitro were tested for their percolative ability in soil at 0.5, 5.0, 10.0, 15.0 and 20.0 cm depth and concentrations 0.025, 0.05, 0.1 for systemic fungicides and 0.12, 0.25 and 0.3 for non-systemic fungicides. Carbendazim registered the maximum mycelial inhibition (71.93%) at all the concentrations. Higher concentration of both systemic (0.1) and non-systemic fungicides (0.3) and shallow soil depths (0.5, 5.0) were more effective in maximum mycelial inhibition. Of the fungicides used as drenching, combination of mancozeb (0.1%) and carbendazim (0.25%) was effective in managing root rot of A. catechu seedlings. The seedlings drenched twice with all the fungicides showed lesser disease as compared with the seedlings receiving single application of fungicides.